Analysis of Tall Structure Project Considering Effect of Diagrid and Hybrid Diagrid Members : A Review - Yadav, Prafull Kumar; Malviya, Pratiksha (International Journal of Scientific Research in Civil Engineering, 2019)
Skyscraper development involves various complex factors such as economics, aesthetics look, technology, municipal regulations, and politics. Among these, economics has been the primary governing factor. For high rise building, the structural design is generally governed by its lateral stiffness. Diagrid structures carry lateral seismic loads much more efficiently by their diagonal member’s axial action in comparing with conventional orthogonal structures for tall buildings such as framed tubes, A diagrid structure provides great structural efficiency without vertical columns have also opened the new aesthetic potential for tall building architecture. Diagrid has a good appearance and it is facilely apperceived. The configuration and efficiency of a diagrid system reduce the number of the structural element required on the façade of the buildings, therefore less obstruction to the outside view. The diagrid system structural efficiency also helps in avoiding interior and corner columns and therefore allowing significant flexibility with the floor plan. The magnitude and intensity of seismic forces are varying from region to region causing moderate to severe destructive energy on engineering properties as well as rising to great economic losses and threat to life. In this paper we are presenting the past development took place in the field of lateral load resisting members. We are presenting literature review of past researches related to diagrid technique.
Keywords: Skyscraper; Diagrid Structure; Destructive Energy; DIAGRID